2010
DOI: 10.1093/jpepsy/jsq054
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Symptoms of Depression and Anxiety in Mothers of Infants with Congenital Heart Defects

Abstract: The results elucidate the relationship between infants' CHD severity and maternal symptoms of depression and anxiety, possibly identifying a specifically vulnerable patient dyad in need of postoperative interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 36 publications
5
68
1
2
Order By: Relevance
“…This is in line with previous studies showing higher rates of anxiety, depression or post-traumatic stress disorder in mothers of children with CHD (Lawoko & Soares, 2002. As previous studies with samples from the MoBa have shown, mothers of children with severe CHD are most probably at the highest risk (Solberg et al 2011(Solberg et al , 2012. This suggests that a considerable share of mothers may need psychological support after giving birth to a child with CHD.…”
Section: Mental Health Of Children With Chd and Their Motherssupporting
confidence: 92%
“…This is in line with previous studies showing higher rates of anxiety, depression or post-traumatic stress disorder in mothers of children with CHD (Lawoko & Soares, 2002. As previous studies with samples from the MoBa have shown, mothers of children with severe CHD are most probably at the highest risk (Solberg et al 2011(Solberg et al , 2012. This suggests that a considerable share of mothers may need psychological support after giving birth to a child with CHD.…”
Section: Mental Health Of Children With Chd and Their Motherssupporting
confidence: 92%
“…A recent study also reported that 14% of parents of infants with CHD had borderline state anxiety scores, and 5% of parents had significant levels of both state and trait anxiety at the time of hospital discharge [34]. Mothers of infants with severe CHD have also been reported to have significantly higher levels of psychological distress than a control group of mothers of healthy infants at 6, 18, and 36 months postpartum [35][36]. Overall, the evidence suggests that parents of infants admitted to the NICU are at risk of psychological distress.…”
Section: Introductionmentioning
confidence: 96%
“…These challenges, or stressors, can relate to the child's illness and the child's specific characteristics, as well as to personal and socioeconomic factors. For example, parents tend to find the diagnosis of their child with CHD, (15) as well as the hospitalisation, (14,15) cardiac surgery and intensive care unit stay (12,(14)(15)(16)(17) to be extremely stressful. Moreover, some children with CHD may also exhibit excessive irritability and behavioural difficulties that make them more difficult to parent.…”
Section: Introductionmentioning
confidence: 99%
“…(2,14,15,18,24) For many parents the chronic health problems faced by their child place them at a high risk of experiencing ongoing stress. (1,17,27) The effects of these ongoing stressors accumulate over time, and affect parents' ability to adapt, undermining their own health and wellbeing, as well as their family's functioning. (2,6) More than a third of parents of children with CHD have been found to exhibit poor adaptation.…”
Section: Introductionmentioning
confidence: 99%